2016
DOI: 10.1007/s10528-016-9782-5
|View full text |Cite
|
Sign up to set email alerts
|

Additive Antiatherogenic Effects of CETP rs708272 on Serum LDL Subfraction Levels in Patients with CHD Under Statin Therapy

Abstract: Recently, subfraction analysis of serum low density lipoprotein (LDL) is considered to be a better predictor of the risk of coronary heart disease (CHD) compared to the other lipid parameters. The aim of this study was to examine the effects of the HDL-associated Taq1B (rs708272) SNP of cholesterol ester transfer protein (CETP) gene on serum LDL subfractions in patients with CHD. Serum lipid levels were measured enzymatically and LDL subfraction analysis was carried out by the Lipoprint System (Quantimetrix, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Many studies have shown that gene polymorphisms in uence T2DM therapeutic effects [16][17][18][19][20][21][22][23]. SNPs in the HTR3B, HTR7 or ABCB1 genes were associated with myalgia or liver injury [16,22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that gene polymorphisms in uence T2DM therapeutic effects [16][17][18][19][20][21][22][23]. SNPs in the HTR3B, HTR7 or ABCB1 genes were associated with myalgia or liver injury [16,22].…”
Section: Resultsmentioning
confidence: 99%
“…APOE and HMGCR mutations were associated with LDL-C levels [17,20]. CETP, KIF6, SLCO1B1, and CYP2C9*3 were related to the statin effect [18,19,21,23]. To check genetic polymorphisms in Chinese T2DM patients, HTR3B (rs2276307, A > G), APOE (rs7412, c.526C > T), APOE (rs429358, c.388T > C), CYP2C9*3 (rs1057910, c.1075A > C), KIF6 (rs20455, c.2155T > C), HMGCR (rs17238540, T > G), HMGCR (rs17244841, A > T), ABCB1 (rs2032582, c.2677G > T/A), HTR7 (rs1935349, C > T), SLCO1B1 (rs4149056, c.521T > C), and CETP (rs708272, G > A) were detected by the MassARRAY system before patients underwent statin therapy ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the effects of the cholesterol ester transfer protein (CETP) variation on LDL subfraction could change in conditions such as coronary heart disease (CHD) and statin therapy. This was based on the findings [27] that the CETP rs708272 single nucleotide polymorphisms together with statin therapy may show a favourable effect on antiatherogenic LDL-1 and large-LDL subfractions in CHD patients with an atherogenic effect on large LDL subfraction in healthy patients.…”
Section: Effects Of Different Drug Classes On Small Dense Ldlmentioning
confidence: 99%
“…Statins are a common prescription medication for cholesterol reduction, and several intervention trials with statins have demonstrated the bene cial effect of lowering LDL-C in both primary and secondary CVD prevention, especially in subjects with T2DM [15,16]. To ensure the T2DM treatment effect, genetic testing was recommended to patients before medication administration [17][18][19][20][21][22][23][24]. SNPs in the HTR3B and HTR7 genes were signi cantly associated with the myalgia score and may affect the development of myalgia in statin-treated patients [17].…”
mentioning
confidence: 99%
“…ABCB1 (rs2032582: 2677G > T/A) was signi cantly associated with atorvastatin-induced liver injury (p = 0.00068) [23]. CETP rs708272 SNP together with statin therapy may show a favorable antiatherogenic effect [24].…”
mentioning
confidence: 99%